2016
DOI: 10.17139/raab.19.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Genetic History of the Classic Period of Teotihuacan’s Burials in Central Mexico

Abstract: The ancient city of Teotihuacan was a great urban and ceremonial center, whose population grew exceptionally during the Classic Period (300-700 AC). Settlement patterns, culture and burials have indicated an occupation that consisted of groups of neighboring apartment compounds or barrios. We investigated the genetics of three apartment compounds in the Teotihuacan Valley through ancient DNA analysis to prove multiethnicity during the Classic Period. Amerindian mitochondrial haplogroups were identified in 10 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…While soil 87 Sr/ 86 Sr values in a given geologic zone may vary greatly due to the distinct strontium concentrations and weathering profiles of minerals in the underlying bedrock [34,71], only a proportion of soil strontium is available to plants. As such, plant 87 Sr/ 86 Sr values provide a consistent average of local bioavailable strontium within a 4, the Gulf Coast Plain (6), the Central Plateau (7), the Sierra Madre de Chiapas (10), and the Yucatán Platform (11). Sites included in the study are indicated by black dots.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…While soil 87 Sr/ 86 Sr values in a given geologic zone may vary greatly due to the distinct strontium concentrations and weathering profiles of minerals in the underlying bedrock [34,71], only a proportion of soil strontium is available to plants. As such, plant 87 Sr/ 86 Sr values provide a consistent average of local bioavailable strontium within a 4, the Gulf Coast Plain (6), the Central Plateau (7), the Sierra Madre de Chiapas (10), and the Yucatán Platform (11). Sites included in the study are indicated by black dots.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Researchers have long debated the importance of migration in the cultural development of central Mexico. A number of archaeological [1][2][3][4], morphological [5][6][7][8][9], and genetic [10][11], analyses indicate that the Basin of Mexico attracted multiple waves of migrants from across greater Mesoamerica throughout pre-Hispanic times. Biogeochemical studies of radiogenic strontium ( 87 Sr/ 86 Sr) isotopes have proven effective in directly testing the presence of migrants within the Basin, particularly at the Classic period city of Teotihuacan [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This area used to be the homeland of several Mesoamerican civilisations, including the Classic city of Teotihuacan, the Epiclassic city of Cholula, and the Postclassic Toltec, Tepanec, and Aztec Empires [ 11 ]. Some aDNA studies have focused on this region, including individuals from the Postclassic period carrying haplogroups A and B at higher frequencies ( Table 2 ) [ 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 63 ].…”
Section: Basin Of Mexicomentioning
confidence: 99%
“…On the other hand, some neighbourhoods were multi-ethnic settlements. Aguirre-Samudio and colleagues [ 51 ] examined 36 individuals from three different multi-ethnic neighbourhoods (San Sebastián Xolalpan, La Ventilla, and San Francisco Mazapa). They found that the most frequent mtDNA haplogroup was A (58%), followed by haplogroups B (25%), C (14%), and D (3%).…”
Section: Basin Of Mexicomentioning
confidence: 99%
See 1 more Smart Citation